Penerapan Etika Bisnis Islam dalam Komunikasi Pemasaran di PT Kainratu Jepara - Sa'diyah, Mahmudatus; Sukmawati, Dien Ajeng (JIOSE: Journal of Indonesian Sharia Economics, 2025)
This study aims to determine the implementation of Islamic business ethics and to determine marketing communication at PT Kainratu Jepara. This research is a qualitative study with a case study approach. The research data collected were obtained through observation interviews with the owner, employees, and consumers of PT Kainratu Jepara. The results obtained from this study indicate that the implementation of Islamic business ethics in marketing communication at PT Kainratu has been implemented by prioritizing the principle of monotheism, the principle of balance, the principle of free will, the principle of responsibility, and the principle of ihsan. And its relationship with marketing communication is also in accordance with good marketing principles, namely paying attention to the principles of advertising, personal selling, sales promotion, public relations, and direct marketing where the service is carried out honestly and friendly.